2017
DOI: 10.3892/mmr.2017.7941
|View full text |Cite
|
Sign up to set email alerts
|

Repeated inhalation of sevoflurane inhibits the information transmission of Purkinje cells and delays motor development via the GABAA receptor ε subunit in neonatal mice

Abstract: General anesthesia is widely used in pediatric surgery, although the influence of general anesthesia on cerebellar information transmission and motor function is unclear. In the present study, neonatal mice received repeated inhalation of sevoflurane, and electrophysiological alterations in Purkinje cells (PCs) and the development of motor functions were detected. In addition, γ-aminobutyric acidA receptor ε (GABAA-R ε) subunit knockout mice were used to investigate the mechanism of action of sevoflurane on ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Exposure to sevoflurane increased iron content in hippocampal neurons compared with cells not exposed to sevoflurane [ 29 ]. Sevoflurane enhances oxidative stress in the neonatal rat brains and induces ROS production and neuronal cell death [ 30 ]. However, it is unknown whether sevoflurane can affect brain injury after liver transplantation in young rats by modulating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to sevoflurane increased iron content in hippocampal neurons compared with cells not exposed to sevoflurane [ 29 ]. Sevoflurane enhances oxidative stress in the neonatal rat brains and induces ROS production and neuronal cell death [ 30 ]. However, it is unknown whether sevoflurane can affect brain injury after liver transplantation in young rats by modulating ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, even at low doses, propofol treatment reduces the levels of Notch1 and Jagged1, which promotes Bergmann glial cell reduction and Bergmann abnormal processes, further slowing down granule cell migration and weakening of cerebellar PC development (33). Fang et al noted that the inhalation of sevoflurane seemed to inhibit sensory information transmission in the cerebellar cortex and had a partially dose-dependent effect, further delaying cerebellar motor function development (34). Moreover, inhaled anesthetics may also increase the level of small oligomers in the cerebellum (35), such as Aβ peptide aggregates, and impair learning and memory function in AD.…”
Section: Effect Of Cerebellar Dysfunction After General Anesthesia On Admentioning
confidence: 99%
“…Purkinje cells are an important part of the signal transmission (Fang et al, 2018), and dendritic dysfunction can cause the related signal transmission to be blocked. The current study found that the YAP signaling pathway can maintain the normal structure of the Purkinje cell dendrites, thereby promoting normal cerebellum morphology and motor coordination function (Liu et al, 2017).…”
Section: Yap Ensures Smooth Signal Transmission Via Protecting Purkinmentioning
confidence: 99%